Pengaruh Budaya Sekolah Smart Student Terhadap Kemampuan Dasar Siswa SDIT Al Ibrohimi - Ramadhani, Isnaini Farikha; Ashari, Slamet (Manajemen Pendidikan, 2024)
Schools are not merely institutions for learning; they are pivotal in molding character and fostering competitive youth. Primary education, particularly, lays the cornerstone for children's academic, social, and character development. In the contemporary educational landscape, literacy, numeracy, and religious education stand as indispensable pillars, essential not only as basic skills but also as the bedrock for academic prowess and daily life. Character development takes precedence, offering a sturdy moral and ethical scaffold for students. However, amidst the ever-changing times, the task of providing comprehensive education grows more intricate, prompting schools to embrace innovative programs that seamlessly integrate crucial elements such as literacy, numeracy, religious education, and character building. Enter the SMART Student Program, designed to bolster students' literacy, numeracy, and tahfidz skills while nurturing robust character traits. This study delves into the SMART Student Program's impact on enhancing students' literacy, numeracy, and tahfidz skills and its repercussions on character development. Employing a quantitative descriptive approach, data from questionnaires, program outcomes, and student attendance spanning two months are analyzed. Regression and correlation analyses reveal a significant positive correlation between the SMART Student Program and students' basic competencies, underscoring the pivotal role of school culture in shaping student character and academic performance The study reveals a significant correlation between school culture and students' basic competencies, supported by a significance value < 0.05. This study furnishes empirical evidence underscoring the significance of school culture in character formation and advocates for educational paradigms centered on character values.